Conservation biology at universiti Malaysia Sabah, Kota Kinabalu, Malaysia (Denmark, 2000)
This important reference examines the logic and methods for the diagnosis and treatment of species extinctions and declines.
Keywords: Bảo tồn sinh vật,Conservation biology